Desenvolvimento e avaliação toxicológica de filmes proteicos com adição de nanofibras de celulose para recobrimento de frutos - Corrêa, Tassiane Regina Alves (2013)
Brazil is a major producer of fruit, but the losses related to postharvest handling are considerable high, and it is important to develop methods to reduce them. Analysis techniques were used is the application of edible coatings in order to increase the shelf life of the fruit. This study evaluated the use of zein based films, storage proteins from corn, with the addition of plasticizers and cellulose nanofibers, for covering pears and apples. The zein are hydrophobic proteins and can form a barrier against moisture loss and gas exchange, thus reducing the rate of fruit respiration and consequently increasing it`s shelf life. The filmogenic solutions tested were obtained using 4% zein with addition of different concentrations of cellulose nanofibers and plasticizers. The solutions were applied on apples and pears by immersion. Fruits were evaluated for weight loss, appearance and texture, where it was shown that the optimal concentration was 4% + 0.1% zein cellulose nanofibers + 0.5% oleic acid, as obtained an increase of about 30 days the shelf life of fruit in addition there was better preservation of fruits in natural color and texture compared to other concentrations. For this we use techniques: colorimetry, texturometer and monitoring of mass loss. For characterization of the films were used analysis techniques and contact angle atomic force microscopy, where we also observe that the best result for these two parameters was the movie 4% zein + 0.1% cellulose nanofibers and 0.5% oleic acid, because the films were less hydrophilic and more homogeneous. To evaluate the toxicity of produced film an experiment was conducted with male Wistar rats that were divided into two groups: the first group was fed with feed coated with filmogenic solution, and the second group received a diet without coating. During the experiment they documented the intake of food and water, and collected all excrement. After the experiment various organs were collected for analysis. The results of this experiment indicated that the solution filmogenic showed no toxic effect on the mice. The results of the experiments with the fruit specified the solutions were more efficient for the preservation of fruit quality in the study.